Implementation Science, Behavior Analysis, and Supporting Evidence-based Practices for Individuals with Autism. Issue 1 (2nd January 2020) - Odom, Samuel L.; Hall, Laura J.; Suhrheinrich, Jessica
ABSTRACT: Although applied behavior analysis researchers have created efficacious treatment and intervention practices for children and youth with autism spectrum disorder (ASD), there is a gap between research and practice. Implementation Science (IS) and Organizational Behavior Management (OBM), based with Applied Behavior Analysis, are two parallel fields that could close this gap. This paper provides descriptions of both IS and OBM, highlighting their commonalities and unique features. The paper concludes with examples of how researchers have used IS and OBM to promote practitioners' use of evidence-based practices and services for children and youth with ASD.